Farewell ritual in relatives of patients with a terminal disease - Lisbôa, Márcia Lucrecia; Crepaldi, Maria Aparecida (Paidéia (Ribeirão Preto), 2003)
A qualitative research about the therapeutic effects of the farewell ritual at the imminence of death, in relatives of patients with a terminal disease. Eight families of patients hospitalized at a General Hospital were studied. It has used the clinical method, the case study technique and interviews after the patient's death, with the data analyzed through the Content Analysis method. The results show that the relatives presented their farewell through verbal and non-verbal communication, religion, "liberation", "being together", bringing other relatives, and they were favorable to the ritual realization, highlighting the learning, the privilege in participating and the psychology guidance's importance. As difficulties, they reported the feelings of pity, sadness, anguish and the lack of courage. The rituals effects were: comfort, tranquility; impotence, blames and sadness relief, death acceptance help; relatives and patient closeness; the communication openness between them, conditions improvement to deal with mourning, relationships redefinition with the person still alive.